ALWASILAH’S VIEW ON LANGUAGE PLANNING IN INDONESIA - Inawati, Iin (Bappeda Kabupaten Pringsewu, 2018)
Language planning is one of national programs for the country that want its verbal communication system run well to support the other aspects of life. Adeng Chaedar Alwasilah is one of Indonesian scholar that concerns about language planning. In his three books, Pokoknya Rekayasa Literasi (2012), Pokoknya Sunda: Interpretasi Untuk Aksi (2006) and Language, Culture, and Education: A Portrait of Contemporary Indonesia (2001), he proposes that Literacy is the key word in language planning. Even the succeed of language education can be measured by measuring the literacy capacity of the people. Indeed, Alwasilah claims that literacy is the vital aspect of language education and culture.